2021
DOI: 10.3390/osteology1020010
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Gender on Occurrence of Aseptic Loosening and Recurrent PJI after Revision Total Knee Arthroplasty

Abstract: Background: Periprosthetic joint infection (PJI) is a common yet severe complication after total knee arthroplasty (TKA). Surgical intervention and antibiotic therapy are obligatory to achieve successful, infection-free outcome. Compared to the outcomes after primary TKA, prosthesis failure rates are drastically increased after PJI-dependent revision surgery. Recurrent PJI and aseptic loosening are the most common reasons for prosthesis failure after revision TKA. An open question is the influence of the patie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…For revision surgery, one-, two-, or multiple-stage exchange surgery was performed as previously described [15,33,34]. After removal of the infected prosthesis, patients received a temporary, antibiotic-loaded cement spacer between stages in case of two-or multiple-stage exchange surgery.…”
Section: Treatmentmentioning
confidence: 99%
“…For revision surgery, one-, two-, or multiple-stage exchange surgery was performed as previously described [15,33,34]. After removal of the infected prosthesis, patients received a temporary, antibiotic-loaded cement spacer between stages in case of two-or multiple-stage exchange surgery.…”
Section: Treatmentmentioning
confidence: 99%
“…While the pathomechanisms responsible are largely unknown, osteoimmunological pathways in general and a proinflammatory environment in particular have been suggested to be pivotal for disease progression and long-term failure 6 , 7 . Further evidence of the role of altered bone metabolism is provided by sex-dependent differences, in that women are significantly more at risk for aseptic loosening after PJI revision surgery 20 . To our knowledge, the present study is the first to investigate the effect of PJI on the surrounding skeletal component in humans and to provide evidence of the occurrence of osteitis in the bone surrounding the total knee replacement.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found prosthesis failure rates after revision arthroplasty to be significantly elevated in patients with rheumatoid arthritis, further stressing the need for a more personalized diagnostic and therapeutic approach in these patients. Similarly, prosthesis survival rates after revision arthroplasty have been found to be significantly decreased in non-rheumatoid arthritis patients [ 11 , 12 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In any of these cases, treatment is an enormous burden for patients [ 9 ]. In addition to surgical intervention, exchange arthroplasty can significantly impact joint function, cause pain, and has an increased risk of prosthesis failure [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%